Evolution and Regulation of Telecommunication and Internet in India - Chauhan, Poonam; Mathew, Jaya (Law, State and Telecommunications Review, 2023)
[Purpose] To examine the advancement of nation-wise internet access in the context of policy and regulations that facilitated the transformation of Indian telecommunication. It analyzes government policies on the development of internet infrastructure, technical standards, content, security and digital inclusion. [Methodology/Approach/Design] Review of Indian regulations and Policy measures governing the evolution of internet and telecommunication sector. Study of Telecom Regulatory Authority of India Act,1997 and subordinate legislations. The study of draft Indian Telecommunication Bill, 2022. [Findings] The evolution of the Internet is credited with progressive convergence of the telecommunications, information technology, and broadcast media. This has led to new paradigms of competition, price wars, contesting licensing and tariffs agreements. The paper attempts to illustrate the regulations that govern these evolving paradigms. [Practical Implications] The Indian telecom sector has more than one billion subscribers and makes significant contribution to GDP of the nation. The Indian government has agreed upon a multi-stakeholder’s approach for internet governance in India. The policy reflects a supportive stand on net neutrality and is shaping digital surveillance on the matters of national security. [Originality/Value] This paper is a unique attempt to describe the policy and legislations that govern the fast-growing sectors of internet and telecommunication in India. The restructuring of the regulatory and legal framework for telecommunication sector is being undertaken by the government to protect the consumer and national interest.